2021
DOI: 10.1080/2372966x.2021.1907221
|View full text |Cite
|
Sign up to set email alerts
|

Social, Emotional, and Behavioral Assessment Within Tiered Decision-Making Frameworks: Advancing Research Through Reflections on the Past Decade

Abstract: Schools play a critical role in service delivery related to students' social, emotional, and behavioral (SEB) health. A foundation for effective SEB service delivery includes capacity to identify students in need of support, differentiate which supports are needed, and monitor students' responsiveness to intervention. Assessment is critical for each of these goals, providing the data needed to make effective decisions across the continuum of service delivery. This special issue provides opportunity to reflect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Youth at-risk identified from the current study showed the highest levels of risks among four risk profiles across social, emotional, behavioral, and academic domains. Through this result, MTSS, a comprehensive framework aimed to address the interplay of social, emotional, behavioral, and academic functioning in the classroom ( 24 , 25 ), can be suggested as the most suitable educational service for youth at-risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Youth at-risk identified from the current study showed the highest levels of risks among four risk profiles across social, emotional, behavioral, and academic domains. Through this result, MTSS, a comprehensive framework aimed to address the interplay of social, emotional, behavioral, and academic functioning in the classroom ( 24 , 25 ), can be suggested as the most suitable educational service for youth at-risk.…”
Section: Discussionmentioning
confidence: 99%
“…Youth at-risk identified from the current study showed the highest levels of risks among four risk profiles across social, emotional, behavioral, and academic domains. Through this result, MTSS, a comprehensive framework aimed to address the interplay of social, emotional, behavioral, and academic functioning in the classroom (24,25), can be suggested as the most suitable educational service for youth at-risk. It was also found that the M-SEB group showed higher risks in aggression, social withdrawal, and depression than in academic behavior and academic motivation, while the M-ACA group indicated the opposite result.…”
Section: Risk Profiles Of Korean Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…EIS and its local norming approach were designed intentionally to get schools and adults to focus on the very contexts that create educational inequities, rather than situating problems within youth (Dowdy et al, 2010; Kim et al, 2022). We provide evidence in this article that schools use this data to change adult behavior and to approach problems differently.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect of social consequences is to consider how equitable the tool is used across school contexts. When used correctly, universal screening with tools like the EIS have been suggested as an approach to reduce disproportionate special education classifications (Raines et al, 2012) and to promote proactive early identification and contextual supports (Kim et al, 2022). One way to frame equitable use of a tool or framework is to examine how consistently and properly it is applied across different school contexts where known inequities occur.…”
Section: Validity Frameworkmentioning
confidence: 99%